Aurophilic Interactions in [(L)AuCl]...[(L')AuCl] Dimers: Calibration by Experiment and Theory - Andris, Erik; Andrikopoulos, Prokopis C; Schulz, Jiří; Turek, Jan; Růžička, Aleš; Roithová, Jana; Rulíšek, Lubomír (Journal of the American Chemical Society, 2018)
Attractive metallophilic (aurophilic, argentophilic, cuprophilic, etc.) interactions play an important role in arrangement and stabilization of oligonuclear metal ion complexes. We report a combined experimental and theoretical assessment of aurophilic interactions in closed-shell gold(I) dimers. The experimental binding energies were obtained for charged [(LH)AuCl]+...[(L')AuCl] dimers (L is either a phosphine or an N-heterocyclic carbene ligand) in the gas phase. These energies served for benchmarking of correlated quantum chemical calculations (CCSD(T)-calibrated SCS-MP2/CBS method) that were then applied to neutral [(L)AuCl]...[(L')AuCl] dimers. The overall attractive interactions between monomeric units are in the order of 100-165 kJ mol-1 in the charged dimers and of 70-105 kJ mol-1 in the corresponding neutral dimers. In the neutral dimers, pure aurophilic interactions account for 25-30 kJ mol-1, the dipole-dipole interactions for 30-45 kJ mol-1, and the L···L' "inter-ligand" dispersion interactions for 5-25 kJ mol-1. Energy of the aurophilic interactions is thus comparable or even larger than that of strong hydrogen bonds.